Simplified Computational Fluid Dynamics Model for Perforated Mitral Valve - Rudiyanto, Philman Jong; Nuraisyah Amira, Mohd Daman Huri; Kahar, Osman; Mohamad Ikhwan, Kori (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2025)
Introduction: Functional mitral regurgitation (Type I) could occur due to leaflet perforation or cleft. There are risks of functional mitral regurgitation might worsen to degenerative regurgitation and ultimately mitral valve failure. Computational fluid dynamics (CFD), an in-silico method, is proven to have the capability of modeling blood flow in cardiovascular system, particularly in this case for regurgitation flow behaviour. Materials and Methods: This paper presented the application of computational fluid dynamics to evaluate the mitral regurgitation due to mitral valve leaflet perforation by simulating the hypertensive conditions and mitral valve perforation severities. Results: The results show that the amount of blood flow to the left atrium increased with the increased perforation severity and hypertension severity. The increase of perforation severity has caused the average reduction of blood flow percentage of up to approximately 8.01% for severe perforation. Conclusion: Hence, the more severe the hypertension and perforation, the more complications a person may experience. With more blood flow back to the left atrium, it may lead to several complications including hypoxemia and cyanosis.